Rancang Bangun Sistem Untuk Menentukan Jumlah Jam Overtime Pada Produksi Barang Dengan Metode Fuzzy Tsukamoto Di PT BONJU Berbasis Web - Ectwan Pasudewa Kresna Marcthadhan; Dede Muhtar Safari (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
When determining the number of hours of overtime PT Bonju still uses the manual method by only looking at the information on the number of goods obtained (results). This causes the number of hours of overtime that is out of sync, the number of items that are not stable in the warehouse and also causes ineffective production data management. Therefore, the process of determining the amount of overtime is reassessed by the method of calculating the number of requests from buyers, inventory and also the number of goods obtained (results). These 3 variables are used to determine the number of hours of overtime that must be done to cover requests from buyers on one working day. The procedure used in this system is by using the fuzzy tsukamoto method. This method was selected because it has a rule in the form of IF-THEN which is presented on a fuzzy set using a continuous membership function. As a result, the inferred output of each condition is given based on the predicate. Output which is interpreted is the number of hours of overtime that must be done to cover requests from buyers in one day. The application to determine the number of overtime hours by using the Fuzzy Tsukamoto method that the author made turns out not only to be able to calculate the number of overtime hours that will be carried out by the production department but also the amount of inventory needed for the next day and support the running of production.